Safety and efficacy of cell-free and concentrated ascites reinfusion therapy (CART) in refractory ascites: Post-marketing surveillance results. - Norio Hanafusa; Ayako Isoai; Tomoaki Ishihara; Tetsuya Inoue; Ken Ishitani; Taiju Utsugisawa; Toshihiko Yamaka; Tetsuya Ito; Hiroshi Sugiyama; Atsushi Arakawa; Yosuke Yamada; Yasuo Itano; et al. (PLoS ONE)
We performed post-marketing surveillance to evaluate the safety and efficacy of cell-free and concentrated ascites reinfusion therapy (CART). In total, 356 CART sessions in 147 patients at 22 centers were performed. The most common primary disease was cancer (128 cases, 300 sessions). Mean amount of ascites collected was 3.7 L, and mean concentration ratio was 9.2. Mean amount of reinfused protein was 67.8 g (recovery rate, 72.0%). Performance status, dietary intake, urine volume, body weight and abdominal circumference were significantly improved after CART. Body temperature increased significantly, by 0.3°C on average. Concomitant steroids and/or NSAIDs use before reinfusion was significantly and negatively associated with increases in body temperature. Most adverse events were fever and chills. This study examined a large number of patients compared with previous studies, and showed that CART is an effective and relatively safe treatment for refractory ascites, such as malignant ascites.